Rank, income and income inequality in urban China - Björn Gustafsson; Ding Sai (Institute for the Study of Labor (IZA), 2008)
While some workers in China attain senior professional level and senior cadre level status (Chuzhang and above), others attain middle rank including middle rank of professional and cadre (Kezhang). This aspect of the Chinese labor force has attracted surprisingly little attention in the literature, a fact which this paper aims to rectify. We define various segments of the urban population in work-active ages and use data from the Chinese Income Project (CHIP) covering eastern, central and western China for 1995 and 2002. For 2002, persons of high rank make up 3 percent and persons of middle rank make up 14 percent of persons in work-active ages. Factors that affect a person's likelihood of having high or middle rank are investigated by estimating a multinomial probit model. We find that education, age and gender strongly affect the probability of being employed as a worker of high rank. There is relatively little income inequality among workers of high rank as well as among workers of middle rank. Mean income and household wealth per capita of highly-ranked workers developed more favorably than for other segments of the population studied, and personal income is more polarized by segment in 2002 than in 1995. Workers of high rank, and to a lesser degree, workers of middle rank, are among the winners in economic terms while the increasingly large category of non-workers are the losers. Rates of return to education have increased but income function analysis indicates that this provides only a partial explanation for the increased favorable income situation for workers of high and middle ranks.
urn:nbn:de:101:1-2008120229
Keywords: J21; 330; China; rank; income; income inequality; Einkommensverteilung; Erwerbsstatus; Bildungsertrag; Stadt; China